The water effect on the kinetics of the bovine liver catalase - Seixas, Flavio Augusto Vicente; Da Silva, Milene Ribeiro; Murakami, Mario Tyago; Tosqui, Priscilla [UNESP]; Colombo, Marcio Francisco [UNESP] (Bentham Science Publishers, 2011)
Catalase is an enzyme that occurs in almost all aerobic organisms. Its main metabolic function is to prevent oxidative damage to tissues induced by hydrogen peroxide which is a strong oxidizing agent. Catalase is very effective in performing this task, since it has the highest turnover rate among all the enzymes. The properties of catalase have been investigated extensively for many years; however, the role of the solvent molecules in the catalytic reaction of this enzyme has not yet been investigated. Therefore, the objective of this work was to investigate the contribution of the solvent molecules on the catalytic reaction of bovine liver catalase with its substrate H2O2 by the osmotic stress method. As a probe for protein structural changes in solution, the differential number of water molecules released during the transition from free to bound form of the enzyme was measured. These assays were correlated with protein structural data provided by the SAXS technique and crystallographic structures of free and CN̄ bonded enzymes. The results showed that the difference in surface accessible area of the crystal structures does not reflect the variation that is observed in solution. Moreover, catalase is not influenced by the solvent during the catalytic reaction, which represents a lower energy barrier to be crossed in the overall energetics of the reaction, a fact that contributes to the high turnover rate of catalase. © 2011 Bentham Science Publishers Ltd.
Keywords: Catalase; Enzyme kinetics; Osmotic stress method; Protein allostery; Water effect